2017
DOI: 10.1002/jca.21542
|View full text |Cite
|
Sign up to set email alerts
|

A transition from using multi‐step procedures to a fully integrated system for performing extracorporeal photopheresis: A comparison of costs and efficiencies

Abstract: IntroductionThe Pitié Salpêtrière Hospital Hemobiotherapy Department, Paris, France, has been providing extracorporeal photopheresis (ECP) since November 2011, and started using the Therakos® CELLEX® fully integrated system in 2012. This report summarizes our single‐center experience of transitioning from the use of multi‐step ECP procedures to the fully integrated ECP system, considering the capacity and cost implications.Materials and MethodsThe total number of ECP procedures performed 2011–2015 was derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 16 publications
5
35
0
Order By: Relevance
“…Moreover, a very recent update of the same UK consensus group confirmed these indications, indicating fair to good evidence to treat patients with skin, hepatic, and cardiac involvement and poor evidences to treat patients with gastrointestinal/pulmonary and renal involvement. A recent Italian retrospective analysis showed similar results with an overall response of 90% in unselected patients with acute GVHD treated by ECP as their second‐line therapy . With respect to the answer given by our best practice to Question 16, we must consider that most Italian centers use off‐line techniques (this survey reported at least 71% of centers using off‐line, and 54% use off‐line only) that, in harmony with other off‐line cell manipulations procedures, should be carried out respecting the requirements stated by several European directives on this specific field (e.g., European Directives 2004/23/CE, 2006/17/CE, 2006/86/CE).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a very recent update of the same UK consensus group confirmed these indications, indicating fair to good evidence to treat patients with skin, hepatic, and cardiac involvement and poor evidences to treat patients with gastrointestinal/pulmonary and renal involvement. A recent Italian retrospective analysis showed similar results with an overall response of 90% in unselected patients with acute GVHD treated by ECP as their second‐line therapy . With respect to the answer given by our best practice to Question 16, we must consider that most Italian centers use off‐line techniques (this survey reported at least 71% of centers using off‐line, and 54% use off‐line only) that, in harmony with other off‐line cell manipulations procedures, should be carried out respecting the requirements stated by several European directives on this specific field (e.g., European Directives 2004/23/CE, 2006/17/CE, 2006/86/CE).…”
Section: Discussionmentioning
confidence: 99%
“…The current availability of the Therakos Cellex Technology opens new opportunities to have an integrated system (avoiding any further complexity and extra costs related to the need of an accredited cell processing laboratory) that assures fast, safe, effective, and widely applicable procedures with competitive expenses. 5,6 With respect to the chance of starting a prospective study for GVHD prophylaxis, recent publications on small Phase II studies showed some encouraging results for ECP in combination with immunosuppresants. 7,8…”
mentioning
confidence: 99%
“…The ECP procedure consists of three sequential phases: collection of buffy coat, photoactivation with ultraviolet A (UV‐A) light, and reinfusion of treated cells. The procedure can be performed using a “closed” system that incorporates all three phases into one device or with an “open” system that consists of separate instrumentation for the leukapheresis and photoactivation phases …”
Section: Technical Aspects and Mechanisms Of Actionmentioning
confidence: 99%
“…The 8‐MOP formulation is FDA approved and commercially known as UVADEX. 8‐MOP intercalates between DNA strands and forms weak bonds with cellular proteins . The photoactivation phase occurs when the buffy coat/8‐MOP suspension is irradiated.…”
Section: Technical Aspects and Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation